Postmodernism and Japan - Harootunian, Harry D., 1929-; Miyoshi, Masao (Book collections on Project MUSE., 1989)
Postmodernism and Japan is a coherent yet diverse study of the dynamics of postmodernism, as described by Lyotard, Baudrillard, Deleuze, and Guatarri, from the often startling perspective of a society bent on transforming itself into the image of Western "enlightenment" wealth and power. This work provides a unique view of a society in transition and confronting, like its models in the West, the problems induced by the introduction of new forms of knowledge, modes of production, and social relationships.